KOORDINASI KEPALA DESA DAN BPD DALAM PEMBANGUNAN DESA DI DESA SIDAS KECAMATAN SENGAH TEMILA KABUPATEN LANDAK - Fernando Fajar E.42009055 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2022)
This script intend to bring the effective coordination between the head of village and BPD in the rural development at Landak Regency. The title of this script based by the issues of the relation betweet the head of village and BPD that can not harmonious especially in the establishment of APBDes at Landak Regency still can not be optimal. This research use qualitative research model by using the theory of coordination "Tripathi and Reddy". This research do 3 stages of analysis, namely data reduction, data display and drawing conclusions and verification. Research sites is in Sidas Village. The subjects is the head of village chief and the chairman of the village along with The BPD with its members. The conclusion of this research is the coordination still can not be optimal because lack of communication between the head of the village and BPD in rural development.  For that, recommendation to makemore effective coordination is to increase the intensiveness of the communication and necessary to follow the leadership training.Keywords: Coordination, Communication and Leadership.